Implications of prescribing a fixed-dose combination in clinical cardiology practice: a retrospective observational study using a single medical centre database in Korea. Issue 2 (26th June 2017) - Kim, Hyungseop; Yoon, Hyuck-Jun; Park, Hyoung-Seob; Cho, Yun-Kyeong; Nam, Chang-Wook; Han, Seongwook; Hur, Seung-Ho; Kim, Yoon-Nyun; Kim, Kwon-Bae
Abstract : Objective: Fixed-dose combination (FDC) prescribing enhances adherence to medication. However, there are limited data regarding the usefulness of FDC drugs across different risk groups. The aim of this study was to explore the relationship between FDC discontinuation and clinical outcomes. Methods: From January 2008 to December 2014, patients with FDC prescriptions who visited a cardiology outpatient clinic at a tertiary university hospital in Daegu, Republic of Korea were retrospectively identified. The 10-year atherosclerotic cardiovascular disease (ASCVD) risk score and 20 conventional cardiovascular (CV) risk factors were assessed. Patients were classified according to FDC continuation, together with a tertile of 20 risks. CV events were defined as the composite of admission for worsening heart failure or diabetes, stroke, ischaemic heart disease, and CV death. Results: 502 patients were prescribed with one of the following FDC products: calcium channel blocker (CCB) plus angiotensin receptor blockers (ARB), CCB plus statins, and ARB plus diuretics. During follow-up (mean 2.8±2.4 years), 203 discontinuations (40.4%) occurred. FDC-discontinued patients had lower ASCVD risk scores (24.8% vs. 28.8%, p<0.001), and patients with <6 risk factors discontinued FDC frequently. During follow-up, 57 events (11.4%) were reported: 30 (14.8%) in FDC-discontinued patients and 27 (9.1%) in FDC-continued patients (p=0.062). In multivariate models accounting for events, FDC discontinuation (p<0.001) and high ASCVD risk score (p=0.017) were associated with CV events. Conclusions: FDC discontinuation was common among patients attending the cardiology outpatient clinic. Our analyses suggest that FDC discontinuation in patients at high ASCVD risk may have an impact on CV event rates.